INTERACTIVE POWERPOINT MULTIMEDIA INFLUENCE IN SOCIAL STUDIES LEARNING ON CONCEPT UNDERSTANDING OF STUDENT SOCIAL MOBILITY - Dwirahayu, Gita Kartika (International Journal Pedagogy of Social Studies, 2019)
One of the objectives of social studies is to recognize concepts related to people's lives and the environment. Social mobility is one of the material discussed in social studies learning and requires a more comprehensive understanding of students. One effort to improve the understanding of concepts in social studies learning is to use interactive multimedia PowerPoint. Through interactive multimedia PowerPoint, students are expected to be able to observe the concepts contained in learning material by absorbing as much information as possible through their senses so that they can improve the understanding of the concept of social mobility of students in social studies learning. The purpose of this study is to identify understanding of students' concepts when using interactive multimedia PowerPoint in social studies learning at Tasikmalaya 3rd Junior High School. The research method used a quasi experimental method with a nonequivalent control group design design pattern. The subjects of this study were Tasikmalaya 3rd Junior High School students there are class VIII B as the experimental class and class VIII C as the control class. The technique of collecting data is through tests of understanding the concepts of the pretest and posttest. Data analysis techniques using the normality test using chi square, homogeneity test using the F-test, and hypothesis testing using the t-test. The results showed an increase in the experimental class gain score on the three indicators, there are translation, interpretation, and extrapolation were higher than the control class. So that it can be concluded, social studies learning by using interactive PowerPoint multimedia is more effective in improving students' concepts understanding.